Utilization of Nanomaterials in Target Oriented Drug Delivery Vehicles - Mandal, T. K.; Patait, V. (Journal of Scientific Research, 2021)
The present investigation deals with the fundamentals of nanorobots, its fabrication, and possible utilization in a different target-oriented drug delivery vehicles. Details of various types of nanorobots and their specific applications are studied in this research. The use of nanorobots in cancer treatment, target-oriented drug delivery, medical imaging, and in new health sensing devices has also been studied. The mechanism of action of nanorobots for the treatment of cancerous cells as well as the formulation and working functions of some recently studied nanorobots are investigated in this work. This paper reviews the research in finding the suitable nanorobotic materials, different fabrication processes of nanorobots, and the current status of application of nanorobots in biomedical, especially in the treatment of cancers. Superparamagnetic iron oxide nanoparticles (SPIONs) have been observed to be used as novel drug delivery vehicle materials. The future perspectives of nanorobots for the utilization in drug delivery are also addressed herewith.